Motivations for Reading the Left Behind Book Series: A Uses and Gratifications Analysis. Issue 2 (2nd April 2016) - Woods, Robert H.; Skarritt-Williams, Kelly; Chan, Caleb; Waters, Ken; Agodzo, Divine
ABSTRACT: This uses and gratifications study investigates motivations for reading the Left Behind book series and their correlation to media use patterns; religious commitments; and the Conservative Protestant, Mainline, or Catholic Christian background of readers. The survey of 1, 188 readers found that sanctified entertainment and "end times" teaching were the top reasons for reading the series. There was a significant positive relationship between religious media use and spiritual growth/development, content reaction, and accuracy. A significant positive relationship was found between religious commitment and content reaction, and religious commitment and biblical accuracy reading motivations. The study revealed different reading motivations among the various denominations, especially Catholics.